Competition might produce pair‐wise negative correlations of genetic richness, not of abundance. (May 2014) - Prinzing, Andreas
Abstract The co‐existence of closely related species can be explained by lack of competition. But it can also be explained by competition that affects not abundance of but the genetic diversity within the competing species. He & Lamont in this issue show results consistent with this latter explanation. This reminds community ecologists that competition is not a simple process producing simple patterns.